Ultrasound Diagnosis of Fetal Thanatophoric Skeletal Dysplasia： Three Cases Report and a Brief Review - 赵庆红 石华 胡佳琪 王丹 方桂 张玉国 王艳清 杨菁 (Journal of Huazhong University of Science and Technology. Medical sciences, 2017)
Congenital skeletal deformity of fetus varies and may be attributed to a range of reasons. Congenital skeletal deformity seriously affects body function or even leads to neonatal death directly. The disease brings great pain to victim and their family. We reviewed the fetal prenatal ultrasonic data conducted during period from Jan. 2013 to June 2016, and there were 84 fetuses with skeletal abnormalities among 12 000 cases, and 3 fetuses with thanatophoric dysplasia. Our report described and reviewed three common types of thanatophoric dysplasia, aiming to explore the value of standardized prenatal ultrasonic diagnosis of fetal abnormalities in the skeletal system.